Basic reading skills : a case study of an adult with Treacher Collins Syndrome / Lilly S. Kulanthai. - S. Kulanthai, Lilly (2012)
Everyone regardless of age and gender should be given an opportunity to learn, especially to read. Literacy improves lives of people in tremendous ways. However, for individuals with cognitive and memory impairment, learning to read has been a great challenge. In response to this challenge, this single subject case study examined the reading ability of an adult with cognitive and memory impairments, using a combination of five reading strategies. These strategies are: improving word recognition, building fluency, improving reading comprehension, using special remedial methods and using computers to teach reading. The five reading strategies were adapted from the teaching strategies recommended by Janet Lerner (2003), in her book ‘Learning Disabilities: Theories, Diagnosis, and Teaching Strategies’ (p.427-450). The research participant of this study is a 21 year old young woman, Jasmine, who was diagnosed with Treacher Collins Syndrome (TCS), since birth. TCS has caused the participant to have marked cognitive delay, memory impairments, hearing impairment, and speech and articulation difficulties. In her 11 years of schooling in special education classes, she has been learning mainly non-academic subjects and never learnt how to read. Two normal adult learners, aged 35 and 43, of early literacy went through the same learning and testing process as the research participant. They were the control group. Their results were used to compare with the performance, weaknesses and strengths of the research participant’s results. The researcher carried out the intervention for five months for Jasmine at her home. As for the control group, they were taught for a month at the researcher’s home. The data collected during the intervention include the Dynamic Indicator of Basic Early Literacy Skills (DIBELS) assessments’ results, spelling test results, anecdotal notes of the participant’s strengths and struggles in the learning process, and explanation of the participant’s progress from a variety of tasks or exercises that she did during lessons, which were kept in a portfolio. Findings revealed that the intervention which utilized a combination of five reading strategies was effective in increasing the reading skills of a person with cognitive and memory impairment.